Niger : Sixth and seventh Reviews Under the Extended Credit Facility Arrangement, Request for Waivers of Nonobservance of Performance Criteria, Request for Augmentation of Access, and Extension of the Current Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Niger. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Niger's Sixth and Seventh Reviews Under the Extended Credit Facility Arrangement, Request for Waivers of Nonobservance of Performance Criteria (PC), Request for Augmentation of Access, and Extension of the Current Arrangement. Niger's growth slowed in 2015 owing to lower agricultural and natural resource sectors activity. Over the medium term, real economic growth is expected to pick up as major projects in oil and mineral extraction come to fruition. The IMF staff supports the authorities' request for waivers for the unmet PC on domestic financing and domestic arrears repayments at end-December 2014, and that of domestic financing at end-June 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet